Optimization of Ag2S Quantum Dots Decorated ZnO Nanorod Array Photoanodes for Enhanced Photoelectrochemical Performances. Issue 5 (19th May 2021) - Solís-Cortés, Daniel; Jiménez, Francisco Martín; Jauregui, Guillermo; Gau, Daniel; Pereyra, Javier; Henríquez, Rodrigo; Marotti, Ricardo E.; Ramos-Barrado, José Ramón; Dalchiele, Enrique A.
Abstract : The synthesis of Ag2 S quantum dots (QDs) deposited on the surface of electrodeposited ZnO nanorods (NRs) by a successive ionic-layer adsorption and reaction (SILAR) method is reported. A Box-Behnken response surface factorial design was used to organize the experiments conducted and identify the effects of three electrochemical parameters and their potential interactions. These parameters include zinc precursor concentration in the electrolytic bath, the electrolytic bath temperature and the electrodeposition time on the morphological and structural properties of the electrochemically grown ZnO nanorods. Morphological, structural and optical characterizations of these NRs heterojunctions were done. A direct band gap for Ag2 S QDs, tuned between 2.54 and 2.73 eV by varying the SILAR cycle numbers, was determined. The presence of ZnO nanostructures increases the light scattering capability of the samples, allowing an important quantity of diffuse light near the absorption edge of Ag2 S. The photoelectrochemical performance of these ZnO NRs decorated with Ag2 S QDs based photoanodes has been evaluated. The SILAR parameters related to the growth of the Ag2 S QDs that optimize the performance of this photoelectrode are presented. The effect of a ZnS passivation layer has been studied leading to an increase of about 400% in the short-circuit current density after passivation.